Developing Food Sensory Analysis Information System using Waterfall Software Engineering Model - Oliver, Stefanus; Marpaung, Abdullah Muzi; Galinium, Maulahikmah (Swiss German University, 2017)
Food sensory analysis is the terms from the field of Food Technology that has a meaning which means sensory evaluation of food that is conducted by the food sensory evaluators. Currently, food sensory analysis is conductedmanually. It can caus e human errors and consume much ti me. The objective of this research is to build a web based application that is specific for food sensory analysis using PHP programming language. This research followsfour first steps of waterfall software engineering mod el which are user requirements ana lysis (user software and requirements analysis), system design (activity, use cases, architecture, and entity relationship diagram),implementation (software development), and testing (software unit, functionality, validit y, and user acceptance testing). T he software result is well built. It is also acceptable for users and all functionality features can run well after going through those four software testing. The existence of the software brings easiness to deal with the manual food sensory analysis exper iment. It is considered also for the future it has business value by having open source and premium features.